Effectiveness of Resin-Composite Fillings vs. Amalgam Fillings in Restorative Dentistry: A Meta-Analysis on Durability and Patient Satisfaction - Zehra, Anbreen; Rafique, Muhammad Umer; Sohaib, Muhammad; Hafeez Ullah; Khan, Samiullah; Hussain , Mutaqaim (Indus Journal of Bioscience Research, 2025)
Background: The longevity and clinical effectiveness of dental restorations are crucial in restorative dentistry, particularly when comparing resin-composite and amalgam fillings. While amalgam has traditionally been favored for its durability, resin-composites are increasingly preferred due to aesthetic advantages and patient satisfaction. However, variations in failure rates, longevity, and patient-reported outcomes require further investigation. Objective: This meta-analysis evaluates the comparative effectiveness of resin-composite and amalgam restorations, focusing on restoration longevity, failure rates, and patient satisfaction to determine the most clinically effective material for restorative dentistry. Methods: A systematic search was conducted across PubMed, Embase, Cochrane Library, and Web of Science to identify randomized controlled trials (RCTs), cohort studies, and observational studies comparing resin-composite and amalgam restorations. Statistical analyses were performed using Review Manager (RevMan) and Stata software, applying a random-effects model to calculate pooled effect sizes and assess heterogeneity. Results: The meta-analysis included nine studies with a total sample size of 10,000 patients. Composite restorations demonstrated higher patient satisfaction (MD=1.20, 95% CI: 0.50–1.90, p=0.002) compared to amalgam, likely due to aesthetic appeal and improved comfort. Restoration longevity was slightly higher in amalgam restorations, but with moderate heterogeneity (I² = 55%), suggesting variability in study methodologies. Clinical effectiveness analysis favored composite restorations (OR=0.80, 95% CI: 0.70–0.90, p